Effectivity of Whiteboard Animation Proclamation-Based on The Patriotism of Elementary School Students - Samsudin, Asep; Kuswendi, Uus; Wulandari, Medita Ayu; Farihah, Zaqiyah Lailatul (PrimaryEdu : Journal of Primary Education, 2022)
This research aims to analyze the effectiveness of the whiteboard animation proclamation based on the patriotism character of elementary students. This is quantitative with quasi-experimental research. Random cluster sampling with 56 students was used as a sampling technique. The data were collected through patriotism scale tests before and after learning activity. Analysis data techniques used were descriptive and inferential statistics analysis by comparing the average result of the test and t-test. The result shows that the average of students' patriotism in the control class is lower than in the experimental class. The increase of the control class is only 15.05% compared to the experimental class that increased 32.25%. T-test results show that whiteboard animation proclamation-based can influence elementary students' patriotism with a significance value of 0.00 (<0.05). It shows that whiteboard animation is effectively used to improve the patriotism character of elementary school students.